GE_GERICHTE P/615/2020 vom 27. August 2020 - GE Cour de justice (2020)
CHOIX DE L'AVOCAT;AVOCAT DE LA PREMIÈRE HEURE;POLICE;INDEMNITÉ(EN GÉNÉRAL);HONORAIRES;DÉFENSE;AUDITION OU INTERROGATOIRE | CPP.429; CPP.159; LPAv.41 A; LPAv.8 A